Implementasi Technology Acceptance Model terhadap Adopsi Teknologi Artificial Intelligence pada Startup Digital - Margo Purnomo; Erna Maulina; Aulia Rizki Wicaksono; Muhamad Rizal (Jurnal Manajemen dan Kewirausahaan, 2021)
The purpose of this study is to describe and analyze the implementation of the technology acceptance model on the adoption of artificial intelligence technology in digital startups. By using simple random sampling, a sample of 109 out of 143 populations, which are startups in Greater Jakarta, was obtained. Based on an analysis using Structural Equation Modeling (SEM) analysis with the SmartPLS tool. The results show that the adoption of artificial intelligence in digital startups is influenced by attitudes, perceptions of convenience and perceptions of usefulness. Likewise, perceived convenience and perceived usefulness are significantly affected by external pressures.